Flow redirection endoluminal device (FRED) for treatment of intracranial aneurysms: A systematic review. Issue 3 (June 2022) - Waqas, Muhammad; Dossani, Rimal H; Alkhaldi, Modhi; Neveu, Jocelyn; Cappuzzo, Justin M; Lim, Jaims; Khan, Asham; Lazarov, Victoria; Monteiro, Andre; Davies, Jason M; Siddiqui, Adnan H; Levy, Elad I
Introduction: The Flow Redirection Endoluminal Device (FRED; MicroVention) is a dual-layered flow diverter used for the treatment of intracranial aneurysms. The objective of this systematic review was to compile device-related safety and effectiveness data. Methods: The literature from January 1, 2013 to April 30, 2021 was searched for studies describing use of the FRED for intracranial aneurysm treatment irrespective of aneurysm location and morphology. The review included anterior and posterior circulation ruptured and unruptured saccular, fusiform or dissection, and blister aneurysms. MeSH terms related to "flow re-direction endoluminal device" and "FRED for aneurysms" were used. Data related to indication, complications, and rates of aneurysm occlusion were retrieved and analyzed. Results: Twenty-two studies with 1729 intracranial aneurysms were included in this review. Overall reported morbidity was 3.9% (range 0–20%). Overall procedure-related mortality was 1.4% (range 0–6%). Complication rates fell into 5 categories: technical (3.6%), ischemic (3.8%), thrombotic or stenotic (6%), hemorrhagic (1.5%), and non-neurological (0.8%). The aneurysm occlusion rate between 0 and 3 months (reported in 11 studies) was 47.8%. The occlusion rate between 4 and 6 months (reported in 14 studies) was 73.8%. Occlusion rates continued to increase to 75.1% at 7–12 months (reported in 10 studies) and 86.6% for follow-up beyond 1 year (reported in 10 studies). Conclusion: This reviewindicated that the FRED is a safe and effective for the treatment of intracranial aneurysms. Future studies should directly compare the FRED with other flow diverters for a better understanding of comparative safety and effectiveness among the different devices.